Nutritional Characteristic of Snack bar Formulation Based on Snakehead Fish-Sorghum Flour Flakes and Kidney Beans - Bahriyatul Ma'rifah; Ari Pebru Nurlaily; Adhi Wardhana Amrullah (Ghidza: Jurnal Gizi dan Kesehatan, 2023)
Proving supplementary food such as snack bar from high in energy, protein and iron local foods (snakehead fish flour, sorghum and kidney bean) can be used as specific nutrition intervention for CED and anemia in pregnant women. This study aimed to analyze and nutritional characteristic of snakehead fish-sorghum flour flakes and kidney bean snack bar. The experimental method was Completely Randomized Design (CRD) with four ratios of snakehead fish flour-sorghum flakes and kidney beans, namely F1 (50%:50%), F2 (60%:40%), F3 (70%:30%) and F4 (80%:20%). Nutritional characteristic of snack bar was analyzed using One Way ANOVA and Duncan’s further test. The results showed that the difference ratios of snakehead fish flour-sorghum flakes and kidney beans had significant effect on energy, moisture, carbohydrates, fat, protein, zinc, iron and calcium of snack bar (p<0.05). The nutrient content of snack bar F2, F2, F3 and F4 were energy (432,04 kcal; 433,77 kcal; 4329,49 kcal; 437,56 kcal), ash content (3,21%; 3,24%; 3,29%; 3,24%), moisture content (14,46%; 14,71%, 13,35%; 13,72%), fat (20,54%; 21,11%, 19,21%; 21,08%), protein (16,87%; 16,97%; 19,63%; 18,57%), carbohydrates (44,93%; 43,98%; 44,53%; 43,41%), zinc (2,07 mg ; 2,04 mg; 2,07 mg, 2,18 mg), iron (4,35 mg; 6,02 mg; 6,23 mg; 6,76 mg) and calcium (114,21 mg; 130,27 mg; 123,41 mg; 131,83 mg). F4 potentially used as alternative supplementary food for pregnant women with CED and anemia because can be claimed as source of protein and iron product based on food label reference for pregnant women.